(untitled) (Research, Society and Development, 2020)
Occlusopathies are a high prevalence problem characterized by a set of anomalies in the face of deviations in dental alignment, in the relationship between the dental arches and/or between the maxillary bones. The literature shows a direct relationship between occlusopathies and parafunctional habits in early childhood. From this perspective, understanding the etiology of occlusopathies to prevent or intercept these deviations becomes essential, in view of the difficulty in treatment for the correction of future problems. The aim of this study is to verify in the existing literature the relationship between occlusopathies and parafunctional habits in early childhood through studies of malocclusions in children. Scientific articles covering the period 2000 to 2020 of Scholar Google platform, CAPES Periodic Portal, Scientifc Eletronic Library Online (SciELO) were selected, using as keywords: Pediatric Dentistry; Malocclusion; Public Health. Among the deleterious sucking habits, digital, bottle and pacifier suction are among the most common. In addition, the absence of breastfeeding has an intimate relationship with these alterations. Therefore, malocclusion is one of the public health problems in Brazil, being essential public policies to bring information to parents and/or guardians, encourage breastfeeding and make them aware.